2019
DOI: 10.3390/su11072013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Putrescine Application on Peach Fruit during Storage

Abstract: The peach industry faces serious economic losses because of the short “green” life of the fruit at postharvest. In the present study, we investigated the effects of putrescine (PUT) application on the quality characteristics, pattern of ripening, storage behaviour and shelf life of peach fruit during low-temperature storage. The aqueous solution of PUT (0, 1, 2 and 3 mM) was applied to the peach trees at three distinctive stages of fruit growth and development. The fruits, harvested at the commercial stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…In addition, it is widely recognized that the peach contribute to reduce risks of several degenerative human disease (Noratto, Porter, Byrne, & Cisneros‐Zevallos, 2009; Sun, Angelidaki, Wu, Dong, & Zhang, 2019), due the high nutritional values, high levels of antioxidants and anticarcinogenic compounds, carotenoids, and phenolic (Durst & Weaver, 2012). An important characteristic of the peaches is that they deteriorate quickly at ambient temperature (Lurie & Crisosto, 2005) because they are climacteric fruits and have a short storage life period (Abidi et al, 2015; Liu, Cao, & Jiang, 2015), that cause substantial losses in the quality during maturation period, including strong loss of firmness (Abbasi, Ali, Hafiz, Alenazi, & Shafiq, 2019). To extend their commercial life the refrigeration method is overspread (Liu et al, 2015; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is widely recognized that the peach contribute to reduce risks of several degenerative human disease (Noratto, Porter, Byrne, & Cisneros‐Zevallos, 2009; Sun, Angelidaki, Wu, Dong, & Zhang, 2019), due the high nutritional values, high levels of antioxidants and anticarcinogenic compounds, carotenoids, and phenolic (Durst & Weaver, 2012). An important characteristic of the peaches is that they deteriorate quickly at ambient temperature (Lurie & Crisosto, 2005) because they are climacteric fruits and have a short storage life period (Abidi et al, 2015; Liu, Cao, & Jiang, 2015), that cause substantial losses in the quality during maturation period, including strong loss of firmness (Abbasi, Ali, Hafiz, Alenazi, & Shafiq, 2019). To extend their commercial life the refrigeration method is overspread (Liu et al, 2015; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Put also induced seed priming, improving germination, seedling growth, and alleviation to low temperatures [ 163 ]. Concerning fruit quality, Abbasi et al [ 164 ] showed that Put application reduced the rate of fruit softening, fruit weight losses, total soluble solids, titratability, ascorbic acid content, and fading of skin colour during storage in peach fruit during low- temperature storage, regardless of the doses of Put applied, or the time of application in Antirrhinum Majus . Finally, Put may also play a role in plant tolerance to other abiotic stresses, including heavy metal toxicity or UV radiations, which can lead to yield losses and hamper food security as recently reviewed [ 25 , 165 ].…”
Section: Tolerance Responses To Abiotic Stressesmentioning
confidence: 99%
“…The former because, if peaches are sold with high hardness, they may be unsuitable for market if the perceived quality for consumers is inadequate. The latter because storage in a lowtemperature storage range (2.2 C to 7.6 C) may lead to a decrease in quality through dry texture, floury pulp, and flavor loss (known as chilling injury) [14][15][16][17][18][19][20][21].…”
Section: Parametersmentioning
confidence: 99%